Managing business with electronic commerce issues and trends - Gangopadhyay, Aryya 1962- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
This book addresses the importace of e-commerce from developing Web-based systems and pricing to payment systems and budgeting
Includes index. - Title from PDF t.p. (viewed on July 4, 2010)
Keywords: Electronic commerce -- Management